2016
DOI: 10.3892/ijmm.2016.2794
|View full text |Cite
|
Sign up to set email alerts
|

Bergapten exerts inhibitory effects on diabetes-related osteoporosis via the regulation of the PI3K/AKT, JNK/MAPK and NF-κB signaling pathways in osteoprotegerin knockout mice

Abstract: Diabetes, as a serious metobolic disorder, poses global threat to human health. It is estimated that over 50 million individuals are already affected by diabetes. Currently, diabetes-related osteoporosis has been a research hotspot due to its high incidence rate in older individuals. Osteoprotegerin, as an important protein for the prevention of osteoporosis, has been proven to be key to the suppression of osteoporosis. Hence, the loss of function of osteoprotegerin may promote the development of osteoporosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 37 publications
(35 reference statements)
1
33
0
Order By: Relevance
“…Akt1 silencing in mice leads to bone formation disorders in which the differentiation and survival of osteoblasts is inhibited (Kawamura et al, ; Peng et al, ). In contrast, Li et al showed that PI3K/Akt activates the mammalian target of rapamycin (mTOR) to promote osteoporosis (Li, Zhu, Han, & Zhang, ). In this study, the levels of active Akt in the BMSCs of OVX rats were significantly lower than those of healthy rats after 2 weeks of osteogenesis induction.…”
Section: Discussionmentioning
confidence: 99%
“…Akt1 silencing in mice leads to bone formation disorders in which the differentiation and survival of osteoblasts is inhibited (Kawamura et al, ; Peng et al, ). In contrast, Li et al showed that PI3K/Akt activates the mammalian target of rapamycin (mTOR) to promote osteoporosis (Li, Zhu, Han, & Zhang, ). In this study, the levels of active Akt in the BMSCs of OVX rats were significantly lower than those of healthy rats after 2 weeks of osteogenesis induction.…”
Section: Discussionmentioning
confidence: 99%
“…It decreases the content of malondialdehyde (p < 0.05) in the skin of mice volume/trabecular volume ratio (BV/TV), trabecular thickness, and trabecular number. These data must be verified in human studies (Li et al, 2016).…”
Section: In Ratsmentioning
confidence: 92%
“…These data must be verified in human studies (Li et al, 2016). It decreases the content of malondialdehyde (p < 0.05) in the skin of mice volume/trabecular volume ratio (BV/TV), trabecular thickness, and trabecular number.…”
Section: Animal (Level 6) Bergamot and Boxthorn Extractmentioning
confidence: 92%
See 2 more Smart Citations